PENGARUH LINGKUNGAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU (Studi kasus pada Guru SDN Tegal Alur 02) - Wibowo, Ignatius Prasetya Aji (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2024)
This study aims to determine the effect of work environment, work discipline and work motivation on teacher performance. The object of this research is the teacher employees of SDN Tegal ALUR 02 Jakarta. The population in the study amounted to 30 employees. And the sample used was 30 employees at SDN Tegal Alur 02 Jakarta. The sampling method used is the saturated sample. The data collection method is a survey method with the research instrument being a questionnaire. The data analysis method uses Statistical Product and Service Solutions. This study proves that the work environment has a negative and significant effect on teacher performance. Work Discipline has a significant positive effect on teacher performance. Work motivation has a significant positive effect on teacher performance.